Insights into the relationship between hydraulic safety, hydraulic efficiency and tree structural complexity from terrestrial laser scanning and fractal analysis - Yonten Dorji; Emilie Isasa; Kerstin Pierick; Juliano Sarmento Cabral; Tashi Tobgay; Peter Annighöfer; Bernhard Schuldt; Dominik Seidel (Trees, 2024)
Key message This research focused on the interplay between tree structural complexity and drought tolerance, unraveling the crucial role of D b as an indicator of hydraulic efficiency and vulnerability in several tree species. Abstract The potential of trees to adapt to drier and hotter climates will determine the future state of forests in the wake of a changing climate. Attributes connected to the hydraulic network are likely to determine a tree’s ability to endure drought. However, how a tree’s architectural attributes related to drought tolerance remains understudied. To fill this gap, we compared the structural complexity of 71 trees of 18 species obtained from terrestrial laser scanning (TLS) with key hydraulic thresholds. We used three measures of xylem safety, i.e., the water potential at 12%, 50%, and 88% loss of hydraulic conductance ( P 12 , P 50 , P 88 ) and specific hydraulic conductivity ( K s ) to assess the trees’ drought tolerance. TLS data were used to generate 3D attributes of each tree and to construct quantitative structure models (QSMs) to characterize the branching patterns. Fractal analysis (box-dimension approach) was used to evaluate the overall structural complexity of the trees ( D b ) by integrating horizontal and vertical extent as well as internal branching patterns. Our findings revealed a significant relationship between the structural complexity ( D b ) and the three measures of xylem safety along with K s . Tree species with low structural complexity developed embolism-resistant xylem at the cost of hydraulic efficiency. Our findings also revealed that the D b had a stronger and more significant relationship with branch hydraulic safety and efficiency compared to other structural attributes examined. We conclude that D b seems to be a robust descriptor of tree architecture that relates to important branch hydraulic properties of a tree.